The “Wheelbarrow Technique” for partial nephrectomy of endophytic small renal mass - Bellamy Brodie; Alvin YM Lee; Henry SS Ho (Urology Video Journal)
Introduction & objectives: Nephron sparing surgery is widely used for the dissection of renal tumours. However, the resection of completely endophytic tumours remains a challenge. Localisation of these tumours is often made difficult due to a limited or complete lack of any external visualisation on the parenchymal surface. It is therefore difficult to determine the optimal location and angle at which dissection should start. Materials & methods: We demonstrate our approach for completely endophytic tumours, termed the ‘Wheelbarrow' technique, with the use of a video case series of robot-assisted laparoscopic partial nephrectomy. While classical convention may dictate entering the renal parenchyma at the edge of the renal tumour with the aims of preserving maximal normal parenchyma, we have found this results in poor vision and difficult enucleation owed to the sharp dissection angle at the tumour apex. Our proposed ‘Wheelbarrow Technique' utilises a less acute dissection angle, aiming towards the deepest aspect of the endophytic tumour. Once this apex is reached, the tumour can easily be retracted upwards with the 3rd robotic arm or laparoscopic assistant. This provides superb visualisation of the tumour/capsule border, facilitating enucleation as well as the easier identification of feeding vessels for ligation. We perform reconstruction with a 2-layer closure, performed with the sliding Hem-olock® technique. Results: All patients recovered well post operatively, being discharged on post operative day 3 without complications including transfusion requirement or urine leak. Histology demonstrated clear cell renal cell carcinoma with clear resection margins. Conclusions: Totally endophytic renal tumours are a challenge for partial nephrectomy. Our proposed technique of Wheelbarrow Dissection aims to provide superior vision, increasing the chances of completing a successful partial nephrectomy, and obtaining an R0 resection.